2022
DOI: 10.1073/pnas.2114094119
|View full text |Cite
|
Sign up to set email alerts
|

Pain hypersensitivity in a pharmacological mouse model of attention-deficit/hyperactivity disorder

Abstract: Clinical evidence suggests that pain hypersensitivity develops in patients with attention-deficit/hyperactivity disorder (ADHD). However, the mechanisms and neural circuits involved in these interactions remain unknown because of the paucity of studies in animal models. We previously validated a mouse model of ADHD obtained by neonatal 6-hydroxydopamine (6-OHDA) injection. Here, we have demonstrated that 6-OHDA mice exhibit a marked sensitization to thermal and mechanical stimuli, suggesting that phenotypes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 79 publications
(110 reference statements)
1
5
1
Order By: Relevance
“…Mechanical and thermal pain sensitivity were assessed with Von Frey and Plantar (Hargreaves’ method) tests, respectively ( Bouchatta et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mechanical and thermal pain sensitivity were assessed with Von Frey and Plantar (Hargreaves’ method) tests, respectively ( Bouchatta et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Neuroimaging studies in ADHD patients identified structural and functional abnormalities in brain networks with a key role of the ACC ( Faraone, 2015 ) that is at the crossroad of executive functions and pain processing ( Garcia-Larrea and Peyron, 2013 ; Hart et al, 2013 ; Sellmeijer et al, 2018 ). We further identified a key role for the ACC-PI pathways in the interaction between ADHD-like conditions and pain sensitization ( Bouchatta et al, 2022 ). Therefore, we focused the present study primarily on the effects of P2X4 deletion in the ACC and on its consequences in the target PI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations